2018
DOI: 10.1371/journal.pone.0206668
|View full text |Cite
|
Sign up to set email alerts
|

Large geographic distance versus small DNA barcode divergence: Insights from a comparison of European to South Siberian Lepidoptera

Abstract: Spanning nearly 13,000 km, the Palearctic region provides an opportunity to examine the level of geographic coverage required for a DNA barcode reference library to be effective in identifying species with broad ranges. This study examines barcode divergences between populations of 102 species of Lepidoptera from Europe and South Siberia, sites roughly 6,000 km apart. While three-quarters of these species showed divergence between their Asian and European populations, these divergence values ranged between 0–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…Percentage-wise, the ranges for intra-and interspecific COI variation we find in our study species are similar to those found in other groups of life, such as moths, beetles, or birds, which commonly show <3% intraspecific and >2% interspecific variation (Kerr et al 2007;Rivera and Currie 2009;Pentinsaari et al 2014;Schmidt et al 2015;Huemer et al 2018). Even though the estimated total number of haplotypes between the three species varies seven-fold, the maximum intraspecific diversity is at most ~3% and all species can be identified reliably using COI.…”
Section: Coi-based Identificationsupporting
confidence: 80%
See 2 more Smart Citations
“…Percentage-wise, the ranges for intra-and interspecific COI variation we find in our study species are similar to those found in other groups of life, such as moths, beetles, or birds, which commonly show <3% intraspecific and >2% interspecific variation (Kerr et al 2007;Rivera and Currie 2009;Pentinsaari et al 2014;Schmidt et al 2015;Huemer et al 2018). Even though the estimated total number of haplotypes between the three species varies seven-fold, the maximum intraspecific diversity is at most ~3% and all species can be identified reliably using COI.…”
Section: Coi-based Identificationsupporting
confidence: 80%
“…A fundamental assumption of species-level research is that sampling specimens from across their range accurately represents intraspecific genetic diversity (Steinke et al 2009;Bergsten et al 2012;Fernandez-Triana et al 2014;Huemer et al 2018). This tenet is based on population-level processes such as genetic drift and selection, which follow the distance decay principle (Nekola and White 1999) resulting in regional differences that increase with geographic distance as the probability of gene-flow between more distant populations decreases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no taxonomic review of the genus other than for species in the Russian Far East (Tshistjakov 1997). DNA 20 sequence diversity indicates the possible presence of additional species in Asia (Huemer et al 2018).…”
Section: (A) Taxonomic Composition and Distributional Characteristicsmentioning
confidence: 99%
“…In our study, we aimed to enhance the insight in the intraspecific variation by adding a third data set, based on mtDNA, and covering all known and supposed intraspecific groups. The 658 bp segment at the 5′-P end of the COI gene (the 'DNA barcode') has proven a reliable species discriminator in animals (Hebert et al 2003;Huemer et al 2014Huemer et al , 2018. In some cases, it was useful in detecting intraspecific diversity too (Lukhtanov et al 2009;Dinca et al 2010;Pauls et al 2010).…”
Section: Introductionmentioning
confidence: 99%